Photothermal property investigation of V2CTx MXene and its use for all-optical modulator - Kwon, Suh-Young; Lee, Jinho; Jhon, Young In; Lim, Geunweon; Jhon, Young Min; Lee, Ju Han (Elsevier BV, 2022)
MXenes, as novel two-dimensional materials, have garnered significant attention in the field of lasers and photonics owing to their outstanding electronic and optical properties. The results pertaining to the photo -thermal properties and nonlinear absorption characteristics of V2CTx MXene presented herein demonstrate the application of photothermal effect-based polarization rotation for all-optical signal modulation. In our analysis, first, the nonlinear absorption coefficient of a V2CTx thin film was measured using an open-aperture z-scan technique. The estimated nonlinear absorption coefficient was approximately-9.26 x 103 cm/GW at 1560 nm. Next, density functional theory calculations were conducted to determine the electronic band structure and optical absorption spectrum of V2CTx MXene. Following this, photothermal properties of V2CTx MXene were characterized in terms of the photothermal effect-based polarization rotation using 980 nm control and 1550 nm probe beams. The power-dependent temperature slope and conversion efficiency of the phase shift were measured to be 0.15 degrees C/mW and 0.02 pi/mW, respectively. Finally, an all-optical modulator was experimentally implemented using the photothermal effect-based polarization rotation. The rise and fall time constants were estimated to be approximately 311 and 321 mu s, respectively.